High‐Fat Diet Modulates Hepatic Amyloid β and Cerebrosterol Metabolism in the Triple Transgenic Mouse Model of Alzheimer's Disease. Issue 3 (18th December 2020) - Bosoi, Cristina R.; Vandal, Milène; Tournissac, Marine; Leclerc, Manon; Fanet, Hortense; Mitchell, Patricia L.; Verreault, Mélanie; Trottier, Jocelyn; Virgili, Jessica; Tremblay, Cynthia; Lippman, H. Robert; Bajaj, Jasmohan S.; et al.
Abstract : Obesity and diabetes are strongly associated not only with fatty liver but also cognitive dysfunction. Moreover, their presence, particularly in midlife, is recognized as a risk factor for Alzheimer's disease (AD). AD, the most common cause of dementia, is increasingly considered as a metabolic disease, although underlying pathogenic mechanisms remain unclear. The liver plays a major role in maintaining glucose and lipid homeostasis, as well as in clearing the AD neuropathogenic factor amyloid‐β (Aβ) and in metabolizing cerebrosterol, a cerebral‐derived oxysterol proposed as an AD biomarker. We hypothesized that liver impairment induced by obesity contributes to AD pathogenesis. We show that the AD triple transgenic mouse model (3xTg‐AD) fed a chow diet presents a hepatic phenotype similar to nontransgenic controls (NTg) at 15 months of age. A high‐fat diet (HFD), started at the age of 6 months and continued for 9 months, until sacrifice, induced hepatic steatosis in NTg, but not in 3xTg‐AD mice, whereas HFD did not induce changes in hepatic fatty acid oxidation, de novo lipogenesis, and gluconeogenesis. HFD‐induced obesity was associated with a reduction of insulin‐degrading enzyme, one of the main hepatic enzymes responsible for Aβ clearance. The hepatic rate of cerebrosterol glucuronidation was lower in obese 3xTg‐AD than in nonobese controls ( P  < 0.05) and higher compared with obese NTg ( P  < 0.05), although circulating levels remained unchanged. Conclusion: Modulation of hepatic lipids, Aβ, and cerebrosterol metabolism in obese 3xTg‐AD mice differs from control mice. This study sheds light on the liver–brain axis, showing that the chronic presence of NAFLD and changes in liver function affect peripheral AD features and should be considered during development of biomarkers or AD therapeutic targets. Abstract : Long‐term high‐fat diet–induced changes in liver function impact peripheral AD features and should be considered during development of biomarkers or therapeutic targets.